Orthodontic bonding and debonding induces structural changes but does not alter the mechanical properties of enamel - Alexis Ioannidis; Spyridon N. Papageorgiou; Iosif Sifakakis; Spiros Zinelis; George Eliades; Theodore Eliades (SpringerOpen, 2018)
Abstract Background The purpose of the study is to investigate the effect of the bonding procedure on the mechanical properties of human enamel. Methods A total of 20 extracted human premolars were included in this study, with the half of each tooth acting as its own internal control. Embedded and horizontally cut specimens were prepared, and two bucco-orally zones were separated. The first enamel zone of each tooth remained untreated. The opposing zone was subjected to simulated bonding and debonding, including etching with 37% phosphoric acid, bonding with primer and flowable composite resin, and subsequent removal of the composite with an adhesive removal bur. The properties tested were (a) elemental composition by energy-dispersive X-ray analysis, (b) mechanical properties of specimens by instrumented indentation testing (Martens hardness, elastic modulus, and elastic index), (c) enamel morphology by low-vacuum scanning electron microscopy, and (d) molecular composition by Raman microspectroscopy. Statistical analysis was performed by one-way mixed-effects analysis of variance at a = 0.05. Results No significant differences could be found in the mechanical properties (Martens hardness, elastic modulus, and elastic index) and elemental composition of intact and treated enamel, with the possible exception of Si traces, which were found only in the latter. Raman analysis revealed no differences between the two surface states while shallow grooves and parallel lines were found on the surface of treated enamel by SEM analysis. Conclusions Under the limitations of the conditions of the study, there were no mechanical properties' alterations on enamel subjected to orthodontic bonding.